Frailty and type of death among older adults in China: prospective cohort study. (9th April 2009) - Dupre, Matthew E; Gu, Danan; Warner, David F; Yi, Zeng
Abstract : Objective To examine the association between frailty and type of death among the world's largest oldest-old population in China. Design Prospective cohort study. Setting 2002 and 2005 waves of the Chinese longitudinal healthy longevity survey carried out in 22 provinces throughout China. Participants 13 717 older adults (aged ≥65). Main outcome measures Type of death, categorised as being bedridden for fewer than 30 days with or without suffering and being bedridden for 30 or more days with or without suffering. Results Multinomial analyses showed that higher levels of frailty significantly increased the relative risk ratios of mortality for all types of death. Of those with the highest levels of frailty, men were most likely to experience 30 or more bedridden days with suffering before death (relative risk ratio 8.70, 95% confidence interval 6.31 to 12.00) and women 30 or more bedridden days with no suffering (11.53, 17.84 to 16.96). Regardless of frailty, centenarians and nonagenarians were most likely to experience fewer than 30 bedridden days with no suffering, whereas those aged 65-79 and 80-89 were more likely to experience fewer than 30 bedridden days with suffering. Adjusting for compositional differences had little impact on the link between frailty and type of death for both sexes and age groups. Conclusions The association between frailty and type of death differs by sex and age. Health scholars and clinical practitioners should consider age and sex differences in frailty to develop more effective measures to reduce preventable suffering before death.